HUBUNGAN ASUPAN ASAM LEMAK OMEGA 3, IMT/U DAN TINGKAT STRES DENGAN TINGKAT KEPARAHAN PREMENSTRUAL SYNDROME (PMS) PADA REMAJA PUTRI TUNAGRAHITA DI KECAMATAN MARGAASIH - Sekar Apsari Aditya, (2020)
Premenstrual syndrome (PMS) is a combination of physical and emotional disorders that affect 20-80% of women of reproductive age that occur in the last 14 days of the menstrual cycle. Until now the cause of PMS is still unknown, many factors contributed to PMS severity, including nutritional intake and lifestyle. This study was aimed to analyze the relation between intake of omega 3 fatty acid, BMI / A, and stress levels in intellectual disability adolescent girls with the severity of premenstrual syndrome in margaasih district. This study was quantitative research by using a cross-sectional design. This study was used a total sampling technique with a sample of 34 respondents. Data were obtained from the filling out of the questionnaire and measurement of body weight and height using digital scales and microtoise. Bivariate analysis was performed by used a chi-square test. The univariate analysis showed the prevalence of premenstrual syndrome in intellectual disability adolescent girls in margaasih district with mild category was 55.9% and the moderate category was 44.1%. Chi-square test results showed a significant correlation between omega-3 fatty acid intake (p-value = 0.005), BMI / U (p-value = 0.007), and stress level (p-value = 0.045) with severity of premenstrual syndrome . The conclusion obtained in this study was that there was a significant correlation between intake of omega 3 fatty acids, BMI / U, and stress levels with the severity of premenstrual syndrome.